Short-term effects of biochar amendment on soil microbial community in humid tropics - Simarani, Khanom; Azlan Halmi, Muhammad Farid; Abdullah, Rosazlin (Taylor & Francis, 2018)
Biochar is known to ameliorate soil fertility and improve crop production but information regarding soil microbiota responses on biochar amendment remains limited. The experiment was conducted to study the effect of biochars from palm kernel (pyrolysed at 400°C) and rice husk (gasified at 800°C) in a sandy loam Acrisol from Peninsular Malaysia. The soil was amended with palm kernel shell biochar (PK), rice husk biochar (RH), palm kernel biochar with fertilizer (FPK), rice husk biochar with fertilizer (FRH), fertilizer and control soil. Soil samples were taken during maize harvesting and were analysed for physico-chemical properties, microbial biomass, microbial abundance and microbial diversity. Increase in pH, moisture content, CEC, organic C, and labile C were recorded in all biochar amended soils. Microbial biomass C was 65% and 36% higher in RH and FRH, respectively, than control. Microbial biomass N was greatest in FPK and FRH with respective increment of 359% and 341% than control. β-glucosidase and xylanase activities were significantly increased in all biochar treated soils than control. A shift in microbial diversity was not detected. The biochar affects the microbial community by altering the soil environment and increasing labile active carbon sources in the short-term amendment.